The surge in working from home in the wake of the COVID-19 pandemic : what are the long-term potentials for academically and vocationally qualified people? - Mergener, Alexandra [Verfasser]; Winnige, Stefan [Verfasser] (My University, 2021)
"Working from Home (WfH) has become a regular model for large numbers of employees during the COVID-19 pandemic. What future developments can be expected? The article investigates this question on the basis of data from the 2018 BIBB/BAuA Employment Survey and via evaluations of online job vacancies (OJV) from the year 2020. It outlines in which occupational groups long-term changes could be indicated for those with vocational and academic qualifications." (authors' abstract; BIBB-Doku)
Homeoffice-Boom im Zuge der Corona-Pandemie : welche Potenziale zeichnen sich langfristig für akademisch und beruflich
Keywords: G 1.2 Arbeitsmarkt; G 2.3.3 Arbeitsformen, Techniken; G 2.3 Wandel von Arbeit & Wirtschaft; 370; BIBB-/BAuA-Erhebung; Arbeitswelt; Pandemie; Telearbeit; Stellenanzeige; Analyse